Sekuritisasi Isu Imigran di Amerika Serikat di Masa Pemerintahan Donald Trump - Usman, Anisa; Darman Moenir, Haiyyu; Jon Nanda, Bima (Hubungan Internasional Universitas Andalas, 2022)
The issue of securitization regarding immigrants in the US is an issue that has become a public discussion since Donald Trump campaign as a US presidential candidate in the 2016 election. He has publicly conveyed xenophobic anti-immigrant rhetoric. Researchers assume that the existence of securitization makes the issue of immigrants a threat that endangers US nationalsecurity. This is done by conveying speech acts to influence public opinion, thus making the issue of immigrants a problem that requires emergency handling or extraordinary policies that have never been carried out by the previous government. This study aims to describe the stagesof the securitization process on the issue of immigrants in the US during the Donald Trump administration. This research was analyzed with the conceptual framework of the securitization stages of Barry Buzan, Waever, and Jaap de Wilde, which consisted of the stage of raising the issue and the stage of convincing the audience. This research method uses a qualitative approach with descriptive-analytical research and uses secondary data sources. This study found that the securitization process begins with the stages of raising issues through the role of the mass media, the influence of the Republican party promoted by Donald Trump, then continues with the stage of convincing the audience through the delivery of speeches by Donald Trump, Sebastian Gorka, Michael Flynn and Jeff Sessions. Then by issuing emergency and securitization measures legitimized by the audience as evidenced by the increasing US public voice supporting the expansion of the US-Mexico border wall.